Situation Report: Romania, 12 November 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu Visits Yugoslavia Papandreou Visits Romania: Athens and Bucharest on Balkan Diplomacy New Reshuffle Selling Workers Their Own Property Romania Moves to Cut Emigration Prostitution in Romania Poor Condition for City Children Anecdotic Realism: The Ceausescu Era in a Literary Caricature